The most common acute poisonings in children - Vukomanović, Predrag; Petrović, Bojana (Archives of Pharmacy, 2022)
Acute poisoning in children is of great sociomedical importance. Most often, they happen due to the carelessness of people who look after them and is caused by the intake of various toxic substancesin the child’s body in large quantities over a short period of time. Depending on the type of toxic substance, general condition and age of the child, as well as intake route, different clinical manifestations occur that can span from severe to lethal outcomes. The most common manifestations are gastrointestinal, followed by cutaneous and ocular, while a small number of children are admitted to the ICU. Even if mortality rate is low, therapeutic approach implies supportive therapy and specific measures. This review paper considers general characteristics of acute poisoning in children based on the relevant literature. The number of reported poisonings in 2018 in the United States of America was 2,621,242, of which 60% of poisonings were in children under the age of 20. The five most common exposures for children 5 years of age and younger were cosmetics/personal care products (12.1%), household hygiene products (10.7%), analgesics (9.04%), foreign bodies (6.87%), and topical preparations (4.69%). In most countries, acute poisoning most often occurs in children under 6 years of age. Prevention is the most important aspect of the fight against acute poisoning in children. It requires a more serious comprehensive approach of the entire society, raising the awareness of parents and guardians about the importance of safe storage of medicines and chemicals in the household.